Involving stakeholders towards service implementation. Co-designing change of practices using a visual language. (28th July 2017) - Overkamp, Tim; Ruijs, Freya
Abstract: Service implementation is complex and multifaceted. In this paper, we focus on change of practices for actors in an organisation as one of these facets. Successful value co-creation requires different service actors to work together. Therefore, successful realisation of change of practices requires these actors to have a shared mental model of (consequences of) such change, both for themselves and for the collaboration with other actors. We argue that collaborative development and use of a visual language can function as boundary object that can facilitate conversations and development of shared understanding regarding service implementation as change of practices, if connotative meaning of the words in the language is defined by those who use it. We use data from a workshop in the context of implementing a change of practices to show how this can work and reflect on what role designers can have in the transition towards service implementation.